2022
DOI: 10.1021/acssensors.1c02452
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Wearable Sensor Inspired by the Neuron Conduction Mechanism through Gold-Induced Sulfur Vacancies

Abstract: Practical application of wearable gas-sensing devices has been greatly inhibited by the poorly sensitive and specific recognition of target gases. Rapid charge transfer caused by rich sensory neurons in the biological olfactory system has inspired the construction of a highly sensitive sensor network with abundant defect sites for adsorption. Herein, for the first time, we demonstrate an in situ formed neuron-mimic gas sensor in a single gas-sensing channel, which is derived from lattice deviation of S atoms i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…The minimum DL is an index to evaluate the practical application of sensors . We can theoretically calculate the signal-to-noise ratio of the sensor. Figure b shows the linear fitting curves of the four sensors.…”
Section: Resultsmentioning
confidence: 99%
“…The minimum DL is an index to evaluate the practical application of sensors . We can theoretically calculate the signal-to-noise ratio of the sensor. Figure b shows the linear fitting curves of the four sensors.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, subtle heterojunction construction has been adopted as another effective strategy to promote the gas-sensing performance. Recently, CuO combined with n -type metal oxides such as WO 3 , SnO 2 , and ZnO , had exhibited a remarkable sensitization effect on H 2 S detection. Also, tungsten disulfide (WS 2 ) as a typical representative of two-dimensional (2D) transition metal dichalcogenides (TMDs) expressed a similar function when in partnership with metal oxides for gas sensing.…”
Section: Introductionmentioning
confidence: 99%
“…In the semiconductor-based gas sensors, defect engineering is a feasible and effective technique to adjust the physicochemical properties of nanomaterials. , First-principles calculations have showed that S-defected SnS 2 exhibits ideal adsorption for CO and C 2 H 2 molecules, suggesting that the vacancy could significantly enhance the chemical reactivity of the gas with the substrate. , Besides, the gas-sensing features could be improved by introducing noble metals to modify the sensitive layer because of spillover effect and electron sensitization effect, which results in an increase in the sensitivity of the sensor. For example, the response of Ag nanoparticle-embedded-ZnO nanorod sensors to 50 ppm ethanol was increased by a factor of 3 compared to the pure-ZnO nanorods . Therefore, it is assumed that further studies on the synergy of the two strategies to enhance the ethanol-sensing performance of pure SnS 2 will be promising.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 First-principles calculations have showed that S-defected SnS 2 exhibits ideal adsorption for CO and C 2 H 2 molecules, suggesting that the vacancy could significantly enhance the chemical reactivity of the gas with the substrate. 23,24 Besides, the gas-sensing features could be improved by introducing noble metals to modify the sensitive layer because of spillover effect and electron sensitization effect, which results in an increase in the sensitivity of the sensor. 25−27 For example, the response of Ag nanoparticle-embedded-ZnO nanorod sensors to 50 ppm ethanol was increased by a factor of 3 compared to the pure-ZnO nanorods.…”
Section: Introductionmentioning
confidence: 99%